Forced internal desynchrony induces cardiometabolic alterations in adult rats. Issue 2 (August 2019) - de Oliveira, Isis Gabrielli Barbieri; Junior, Marcos Divino Ferreira; Lopes, Paulo Ricardo; Campos, Dhiogenes Balsanufo Taveira; Ferreira-Neto, Marcos Luiz; Santos, Eduardo Henrique Rosa; Mathias, Paulo Cezar de Freitas; Francisco, Flávio Andrade; Koike, Bruna Del Vechio; de Castro, Carlos Henrique; Freiria-Oliveira, André Henrique; Pedrino, Gustavo Rodrigues; et al.
Abstract : Disruptions in circadian rhythms have been associated with several diseases, including cardiovascular and metabolic disorders. Forced internal desynchronization induced by a period of T-cycles of 22 h (T22 protocol) reaches the lower limit of entrainment and dissociates the circadian rhythmicity of the locomotor activity into two components, driven by different outputs from the suprachiasmatic nucleus (SCN). The main goal of this study was to evaluate the cardiovascular and metabolic response in rats submitted to internal desynchronization by T22 protocol. Male Wistar rats were assigned to either a control group subjected to a usual T-cycles of 24 h (12 h–12 h) or an experimental group subjected to the T22 protocol involving a 22-h symmetric light–dark cycle (11 h–11 h). After 8 weeks, rats subjected to the T22 exhibited desynchrony in their locomotor activity. Although plasma glucose and insulin levels were similar in both groups, desynchronized rats demonstrated dyslipidemia, significant hypertrophy of the fasciculate zone of the adrenal gland, low IRB, IRS2, PI3K, AKT, SOD and CAT protein expression and an increased expression of phosphoenolpyruvate carboxykinase in the liver. Furthermore, though they maintained normal baseline heart rates and mean arterial pressure levels, they also presented reduced baroreflex sensitivity. The findings indicate that circadian timing desynchrony following the T22 protocol can induce cardiometabolic disruptions. Early hepatic metabolism dysfunction can trigger other disorders, though additional studies are needed to clarify the causes.